Microwave-assisted aging of organic-inorganic hybrid nanocomposite of α-naphthaleneacetate in the lamella of Zn-Al-layered double hydroxide - Hussein, Mohd Zobir; Zainal, Zulkarnain; Yahaya, Asmah; Vui Foo, Dickens Wong (2002)
Microwave-assisted aging Zn-Al-layered double hydroxide with nitrate as the interlayer anion (ZANOL) and its nanohybrid with an organic moiety, α-naphthaleneacetate (ZANAN), was done and the resulting properties of the materials compared. The results showed that intercalation of the α-naphthaleneacetate (NAA) anion into the Zn-Al layered double hydroxide lamella is readily accomplished, resulting in the expansion of the interlayer spacing from 9.0 Å in the layered double hydroxide to 20.0 Å in the nanohybrid. This expansion accommodates the NAA anion of larger size than nitrate, as indicated by its molecular structure. For both methods, the resulting materials afforded a well-ordered organic-inorganic nanolayered structure. The Zn to Al ratio of the resulting nanocomposite is lower than the ratio present in the mother liquor at the beginning of the reaction, which implied less incorporation of aluminum ions from the mother liquor into the inorganic metal hydroxide layers. By using the microwave-assisted method, however, slightly more Al3+ ions were incorporated into the inorganic metal double hydroxide layers. In general, there is not much difference in the physicochemical properties of ZANANs aged by either the microwave or the conventional oil bath method. For both methods, longer aging time slightly enriched the organic content of the resulting nanohybrid and the inorganic Zn to Al ratio remained the same, independent of the aging time.